Imlementation of Health Belief Model to Predict Adherence toward Acupuncture Services in Low Back Pain Patients - Nurcahyo aji legowo; Bhisma Murti; Sumardiyono Sumardiyono (Masters Program in Public Health, Sebelas Maret University, 2025)
Background Adherence in using acupuncture services can reduce the risk of developing more severe low back pain. Low back pain patients who do not receive regular treatment will experience a high risk of injury. This study aims to determine the relationship between the construct of the health belief model and adherence in using acupuncture services. Subjects and Method: This was a cross-sectional study carried at the Surakarta acupuncture clinic in December-March 2024. A sample of 200 low back pain patients was selected using random sampling. The dependent variable was low back pain patients. The independent variables were perceived vulnerability, perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy. Data were analyzed using a multiple logistic regression. Results: Adherence to acupuncture therapy in LBP patients increased with high perceived vulnerability (OR= 2.46; 95% CI= 1.09 to 5.07; p = 0.028), high perceived severity (OR= 4.07; CI 95%= 1.84 to 8.99; p = 0.001), high perceived benefit (OR= 2.57; 95% CI= 1.12 to 5.84; p = 0.024), had cues to action (OR= 2.24; 95% CI= 1.03 to 4.90; p = 0.042), and high self-efficacy (OR= 2.27; 95% CI= 1.03 to 5.00; p = 0.042). It was decreased by high perceived barriers (OR= -0.35; 95% CI= -0.15 to -0.80; p = 0.014). Conclusion: Adherence to acupuncture therapy in LBP patients increases with high perceived vulnerability, high perceived severity, high perceived benefit, had cues to action, and high self-efficacy. It is decreased by high perceived barriers